Croatia’s Protest and Exhibition “Jasenovac — the Right to Remembrance” in the United Nations, on the Occasion of the Holocaust Remembrance Day in 2018 - Nikšić, Ljiljana (Napredak, 2022)
"Јаsenovac – the Right to Remembrance” was the first exhibition of the Republic of Serbia about Jasenovac in the UN, but also the first one with the topic of Jasenovac after the Second World War and, with 7 tons of equipment and exhibits, the most monumental exhibition in the history of the United Nations. It was held in the UN in New York’s East River, from 26 January to 2 February 2018. The director of this exhibition was Professor Gideon Greif, PhD, a world-renowned historian of the Holocaust and an expert for death camps in the Second World War and the Head of the International Expert Group of Historians “GH7 – Stop to Revisionism”, while the coordinator of the Serbian-Jewish academic cooperation and all the segments of the exhibition preparation was Ambassador Ljiljana Nikšić, PhD. The exhibition was opened by First Vice-President of the Government of Serbia and Minister of Foreign Affairs, Mr. Ivica Dačić, in the presence of the children-survivors of Jasenovac and other children camps in the ISC, who spoke for the first time after the Second World War in the United Nations. The Republic of Croatia and the Croatian Ministry of Foreign Affairs, in its full capacity, through all international organizations and in all possible ways tried to stop the exhibition, also by sending a diplomatic protest to the UN Commission, the State Department, the Ministry of Foreign Affairs of Israel and the EU. The Republic of Croatia based its protests (unsuccessfully) on the “territorial principle”, since Jasenovac is situated in its territory. The United Nations took the side of the Republic of Serbia, accepting its argument that the purpose of the exhibition was the remembrance of the victims of Nazism and fascism, and that it was a matter of preserving the culture of remembrance related to the victims of the death camps in the Second World War, to whom the International Holocaust Remembrance Day is dedicated, taking place in the United Nations every year. The Croatian diplomacy conducted a persistent campaign with the UN Commission, with the condition that “negotiations should be initiated between Belgrade and Zagreb” about the exhibition, and that the Serbian ambassador to Zagreb should “receive the approval” from the relevant bodies in the Republic of Croatia, and only afterwards discuss it in the UN. This was followed by the protest of the Serbian side. The exhibition was the product of the Serbian-Jewish academic project. World agencies such as Reuters, Associated Press, Deutsche Welle, Washington Post and others, reported about the protest of the Croatian Ministry of Foreign Affairs, but also wrote in detail about the exhibition and about the camp in Jasenovac, as well as about 57 methods of brutal killing that had been applied in the camp, which placed the exhibition in the focus of the worldwide attention. Immediately after the exhibition opening, on the margins of the OSCE Conference on Combating Anti-Semitism in Rome, the Serbian Minister of Foreign Affairs had a meeting with Pope Francis, but also with the President of the World Jewish Congress, using the occasion to familiarize them with Serbia’s attitudes against the initiative of the Republic of Croatia for the canonization of Ustasha vicar and arch-bishop Aloysius Stepinac, and expressing his concern over Neo-Ustashism in Croatia. The exhibition “Jasenovac – the Right to Remembrance” in the UN brought about significant changes in the approach to Jasenovac, and resulted in the first official visit of a president of Israel. In July 2018, Reuven Rivlin was the first President of Israel who visited Belgrade and Zagreb and, on that occasion, also visited the Memorial Complex of Jasenovac and paid respects to the great martyrs of Jasenovac. During his visit to Belgrade, together with President of Serbia Aleksandar Vučić, he unveiled the plaque with the name of the street dedicated to the founder of modern Zionism, Theodor Herzl, whose father and grandfather were born in Zemun. Moreover, the result of the exhibition was also the Appeal of the World Jewish Congress to Croatian Prime Minister Andrej Plenković to adopt the Law on the Prohibition of the Use of Ustasha Greeting “Ready for the Homeland” and to remove the memorial plaque of the Croatian Defence Forces with the engraved inscription “Ready for the Homeland” from Jasenovac.